2019
DOI: 10.3390/en12142806
|View full text |Cite
|
Sign up to set email alerts
|

Bench-Scale Cultivation of Microalgae Scenedesmus almeriensis for CO2 Capture and Lutein Production

Abstract: In this study, Scenedesmus almeriensis as green microalga was cultivated on bench-scale for carbon dioxide (CO2) capture and lutein production. The autotrophic cultivation of S. almeriensis was carried out by using a vertical bubble column photo-bioreactor (VBC-PBR) with a continuous flow of a gaseous mixture of oxygen (O2), nitrogen (N2), and CO2, the latter in content of 0.0–3.0 %v/v. The liquid phase was batch. S. almeriensis growth was optimized. In addition, lutein extraction was carried out by using acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 64 publications
(48 reference statements)
0
21
2
Order By: Relevance
“…The lutein content obtained in this study, equal to 5.71 mg/g, was lower than the value of 8.54 mg/g reported by Molino et al (2019) who investigated the performance of the same microalgal species using a vertical bubble column photo-bioreactor with a volume to surface ratio (V/S) of 56.6 L/m 2 . The different lutein content can be explained by the different photo-bioreactor configuration in the two research works: V/S ratio = 11.5 L/m 2 (this work) and = 56.6 L/m 2 (Molino et al, 2019).…”
Section: Co 2 Content and Recycled Medium Effects On Extraction Yieldcontrasting
confidence: 85%
See 1 more Smart Citation
“…The lutein content obtained in this study, equal to 5.71 mg/g, was lower than the value of 8.54 mg/g reported by Molino et al (2019) who investigated the performance of the same microalgal species using a vertical bubble column photo-bioreactor with a volume to surface ratio (V/S) of 56.6 L/m 2 . The different lutein content can be explained by the different photo-bioreactor configuration in the two research works: V/S ratio = 11.5 L/m 2 (this work) and = 56.6 L/m 2 (Molino et al, 2019).…”
Section: Co 2 Content and Recycled Medium Effects On Extraction Yieldcontrasting
confidence: 85%
“…The lutein content obtained in this study, equal to 5.71 mg/g, was lower than the value of 8.54 mg/g reported by Molino et al (2019) who investigated the performance of the same microalgal species using a vertical bubble column photo-bioreactor with a volume to surface ratio (V/S) of 56.6 L/m 2 . The different lutein content can be explained by the different photo-bioreactor configuration in the two research works: V/S ratio = 11.5 L/m 2 (this work) and = 56.6 L/m 2 (Molino et al, 2019). On the other hand, the value reported in this work is slightly higher than those reported in microalgae-based lutein studies using batch phototrophic conditions (Sánchez et al, 2008b;Ho et al, 2014;Xie et al, 2014Xie et al, , 2017, while it is comparable with the values reported by Sánchez et al (2008a,b) who studied S. almeriensis growth in a continuous mode.…”
Section: Co 2 Content and Recycled Medium Effects On Extraction Yieldcontrasting
confidence: 85%
“…On the other hand, recent researches to improve the cost of obtaining microalgae has focused on the use of waste and integrating the co-production of high-value compounds [39]. CO 2 sequestration using a biorefinery approach, through interconnection with the cultivation of microalgae, is an interesting idea, since the waste generated from power plants or other industrial facilities is used [34,40]. The residual microalgae biomass, which was rich in protein and carbohydrates, could still be used as a carbon source for anaerobic fermentation in the production of volatile fatty acids, biohydrogen, CO 2 , among others.…”
Section: Of 19mentioning
confidence: 99%
“…Ghosh et al estimated the GHG emissions from landfill sites in Delhi, India, and they pointed out that effective CH 4 recycling is a sustainable waste management scheme [25]. Besides, Carbon dioxide capture and recycling methods such as the production of biobased products through microalgae can be used as effective means of reducing GHG emissions [26,27].…”
Section: Introductionmentioning
confidence: 99%